Bolivia : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper and Statistical Annex identifies the sources of bank problems in Bolivia. It describes the measures to strengthen the system since 1985, and assesses the early results of bank restructuring in 1994-96. The paper highlights that prior to 1985, financial intermediation was subject to extensive controls on both interest rates and the allocation of credit, and hyperinflation distorted bank credit decisions even further. The paper also describes the basic features of the old pension system of Bolivia, and reviews the main innovations of the new system.